Hubungan Religiusitas dengan Penyesuaian Diri pada Santriwati di Pondok Pesantren Mahasiswi Al-Husna Jember - Siti Qomariyah; Emi Wuri Wuryaningsih; Enggal Hadi Kurniyawan (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Students who do not live in a family environment have a greater burden and responsibility independently. In pesantren there are rules that are more binding and strict, especially for new students who need an adaptation process. This study aims to analyze the relationship between religiosity and self-adjustment. This type of research is a quantitative research that uses analytics with a cross-sectional approach. The study population was 302 students in Pondok Pesantren with a sample size of 91 respondents. The sampling technique uses purposive sampling. The research instruments used were the Relief of Islam Scale and the Social Adaptation to College Questionnaire (Cronbach's Alpha 0.89-0.95; 0.66-0.81). Test the research ethics by the KEPK FKG UNEJ. The results showed a religiosity value of 95.21 (± 48.29) and self-adjustment 386.49 (± 64,260). And there is a relationship between religiosity and self-adjustment to students (p = 0,000; r = 0,465; CI: 95%) which shows that the higher the value of religiosity, the better the adjustment in Islamic boarding schools. Religiosity in students is realized in the form of obtaining religious knowledge and practices that have been instilled since the womb. Whereas in the form of adjustments in the form of attending boarding school orientation activities, the time of permission to go home is limited, the obligation to pay off takziran, and the long duration of stay in the pesantren